Finding and investigation of the Kamchatka glaciers - A. Ya. Muraviev (Лëд и снег, 2015)
History of finding and investigation of the present-day glaciers of the Kamchatka Peninsula is described. A degree of our knowledge of such glacier characteristics as the mass balance, sizes, and the area fluctuations for the second half of 20th – beginning of 21st century is discussed. A literature on the Kamchatka glaciations is reviewed. In accordance with purposes of the investigations, methods, and volumes of field researches five periods have been separated in the history.